2003
DOI: 10.1542/peds.111.3.e282
|View full text |Cite
|
Sign up to set email alerts
|

Transient Suppression of Atopy in Early Childhood Is Associated With High Vaccination Coverage

Abstract: Methods. A German atopy risk-enhanced birth cohort of 1314 neonates who were born in 1990 in 5 German cities was studied. A total of 943 children participated in the follow-up visit at 5 years of age. Atopic symptoms and diagnoses (derived from structured interviews), total serum immunoglobulin E, and specific immunoglobulin E against 9 common allergens (CAP Radio-Allergo-Sorbent Test Fluoro-Enzyme Immunoassay) were evaluated. Children were grouped into dose percentiles according to cumulative doses of any vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
60
1
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 24 publications
8
60
1
5
Order By: Relevance
“…A study by Gruber et al (12) revealed no evidence for an allergy-promoting effect of common childhood vaccines in a prospectively monitored atopy risk-enhanced birth cohort. Moreover, children with better vaccination coverage seemed to be better protected against the development of atopy in their second and third years of life.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…A study by Gruber et al (12) revealed no evidence for an allergy-promoting effect of common childhood vaccines in a prospectively monitored atopy risk-enhanced birth cohort. Moreover, children with better vaccination coverage seemed to be better protected against the development of atopy in their second and third years of life.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, children with better vaccination coverage seemed to be better protected against the development of atopy in their second and third years of life. In particular, immunizations against measles and mumps, pertussis, and diphtheria and against tetanus were associated with a transient reduction of atopy, whereas immunization against polio and Haemophilus influenzae had no effect (12). A conflicting study of the effects of vaccination on allergies among children in the United States has reported that diphtheria-tetanus-pertussis vaccination appeared to increase the risk of allergies and related respiratory symptoms (21).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations